EFFECTIVENESS OF VIDEO-LEAFLET PROMOTION ON ADOLESCENTS’ PREMARITAL SEX KNOWLEDGE AND ATTITUDES AT PERTIWI HIGH SCHOOL JAMBY CITY - Alyasha Shaghira; Usi Lanita; Puspita Sari; Silvia Mawarti Perdana (Jurnal Multidisipliner Bharasumba, 2026)
This study investigated the effectiveness of health promotion delivered through video and leaflet media in improving adolescents’ knowledge and attitudes toward premarital sex prevention at SMAS Pertiwi, Jambi City. Using a quantitative quasi-experimental method with a pretest-posttest two-group design, the research involved 48 grade XI students who were equally assigned to a video group and a leaflet group, with 24 participants in each. Data were collected before and after the intervention to assess changes in knowledge and attitudes. The results indicated that both educational media significantly increased students’ understanding and positively influenced their attitudes after the intervention. In terms of knowledge improvement, video and leaflet media produced relatively similar outcomes, suggesting that both were equally effective in delivering information. However, video media demonstrated a stronger impact on shaping adolescents’ attitudes toward premarital sex prevention, likely because audiovisual content was more engaging and persuasive. Overall, both media are useful, video excels.